Malta : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses infrastructure gaps vis-a-vis other EU countries that are most striking in road and energy networks, both in quality and quantity. This is reflected in an unparalleled gap in the approximated public capital stock. Long-term GDP benefits from increasing public investment are estimated to be substantial, ranging between 5u and 18u percent in net present value over 30 years. Malta's authorities have started to tackle these challenges by upgrading and diversifying the energy system and by launching a comprehensive transport strategy. These efforts go in the right direction and should be implemented in a budget-neutral manner to support a further decline in the public debt-to-GDP ratio. Malta's fiscal position has improved considerably in recent years, yet further buildup of fiscal buffers is needed against possible adverse macroeconomic conditions. Therefore, reallocating public spending from current to capital expenditure, as well as making public investment more efficient would help boosting infrastructure.